Channelrhodopsins shed light on a new pathway in absence epilepsy. (January 2012) - Petrou, Steven; Reid, Christopher A
Evaluation of: Paz JT, Bryant AS, Peng K et al. A new mode of corticothalamic transmission revealed in the Gria4 -/- model of absence epilepsy. Nat. Neurosci. 14(9), 1167–1173 (2011). Absence seizures are a common form of epilepsy characterized by sudden behavioral arrest in conjunction with a stereotypical spike-and-wave discharge on electroencephalography. A reciprocally connected network of thalamocortical neurons that normally controls sleep and other functions, misfires to cause absence epilepsy and is perhaps one of the most studied seizure networks. In a recent paper, Paz and colleagues further dissect this network to understand the basis of seizure initiation in a new animal model of absence epilepsy. Exploiting state-of-the-art 'optogenetic'' methodology they systematically isolate monosynaptic connections in thalamocortical nuclei to reveal the key pathological mechanism underlying absence seizures in the Gria4 -/- mouse. The main finding is a reduction in the strength of synapses made by excitatory cortical projection neurons onto the reticular thalamic nucleus. The consequent fall in reticular thalamic nucleus inhibitory neuron output results in less feed-forward inhibition of thalamocortical neurons and an increase in thalamic excitability that is, presumably, sufficient to initiate oscillations and absence seizures. The manuscript adds significantly to our understanding of how absence seizures can initiate by implicating, in this case, a thalamic rather than cortical basis. Further, the demonstration of this mode of circuit activity may have significant implications for how the thalamocortical network behaves physiologically.